Electrolyte for aqueous zinc ion battery and aqueous zinc ion battery

By adding BOC-D-glutamic acid to the electrolyte of an aqueous zinc ion battery, the problem of poor cell cycle stability is solved, inhibiting zinc dendrites growth, corrosion and slowing down hydrogen evolution reaction is achieved, and the cycle life and efficiency of the battery are significantly improved.

CN119542571APending Publication Date: 2025-02-28HENAN UNIV OF SCI & TECH
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411637925.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-15
Publication Date
2025-02-28

AI Technical Summary

Technical Problem

The poor circulation stability of existing water-based zinc ion batteries leads to problems such as zinc dendrites growth, corrosion and hydrogen evolution reaction, which limits the reversibility and cycle life of the battery.

Method used

Add 5~15mM of BOC-D-glutamic acid to the electrolyte to adjust the solvation structure of the electrolyte, modify the zinc negative electrode/electrolyte interface, and generate solid electrolyte membrane SEI in situ on the surface of the zinc negative electrode to inhibit dendrites' growth, resist corrosion, and slow down the hydrogen evolution reaction.

Benefits of technology

The cycle stability of aqueous zinc ion batteries is significantly improved, the cycle life of Zn||Zn symmetrical batteries is extended to 2000h to 5750h, and high efficiency and stability are maintained in the Zn||Cu half-cell.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119542571A_ABST
    Figure CN119542571A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of secondary batteries, in particular to an electrolyte for an aqueous zinc ion battery and the aqueous zinc ion battery. The electrolyte for the aqueous zinc ion battery provided by the invention comprises zinc salt and 5-15 mM of BOC-D-glutamic acid. The BOC-D-glutamic acid (C10H17NO6) is added into the electrolyte, the BOC-D-glutamic acid can adjust the solvation structure of the electrolyte, modify a zinc negative electrode / electrolyte interface and generate a solid electrolyte membrane SEI on the surface of the zinc negative electrode in situ, the solid electrolyte membrane SEI has the characteristics of inhibiting dendritic crystal growth, resisting corrosion, slowing down a hydrogen evolution reaction and the like, the cycling stability of the aqueous zinc ion battery can be greatly improved, and the service life of the aqueous zinc ion battery is prolonged. The cycle life of the ZnZn symmetric battery (5 mA cm < 2 > / 5 mAh cm < 2 >) can reach 2000 h, and the cycle life of the ZnZn symmetric battery (1 mA cm < 2 > / 1 mAh cm < 2 >) can reach 5750 h.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of secondary batteries, and in particular to an electrolyte for an aqueous zinc ion battery and an aqueous zinc ion battery. Background Art

[0002] In the research and development in recent years, with the rapid popularization of mobile communication terminals and electric vehicles and other equipment, the society's demand for efficient and stable electrochemical energy storage systems is growing. Lithium-ion batteries have the most mature technology among many battery systems due to their long cycle life and ideal weight energy density, and have therefore been widely used. However, due to their high cost, safety issues and potential impact on the environment, the further development of lithium-ion batteries has been limited, which has prompted people to urgently seek to develop new non-lithium electrochemical energy storage systems.

[0003] In the exploration of new battery systems to replace lithium-ion batteries, aqueous zinc-ion batteries with zinc as the negative electrode have attracted attention due to their low cost, environmental protection and safety, showing great potential to become a new choice for future electrochemical energy storage systems. Zinc, as an element abundant in the earth's crust, is not only low in cost but also environmentally friendly. Its volume energy density is as high as 5855 mAh cm -3 Aqueous zinc-ion batteries often use zinc sulfate aqueous solution as the electrolyte, but problems such as dendrite growth and side reactions in the zinc negative electrode severely limit the battery's cycle life and commercial prospects. Dendrite growth may not only cause battery short circuits, but may also cause the formation of "dead zinc" due to dendrite breakage. At the same time, the occurrence of hydrogen evolution reaction will also produce a large amount of hydrogen, which will damage the battery structure and may produce by-products, greatly damaging the reversibility and cycle stability of zinc-ion batteries.

[0004] Whether corrosion, hydrogen evolution or zinc dendrite growth, they all originate from the unstable zinc anode / electrolyte interface. Therefore, by rationally regulating the zinc anode / electrolyte interface, the occurrence of side reactions and zinc dendrite growth can be effectively inhibited. In order to improve the reversibility of zinc anode, researchers have conducted a series of innovative studies to improve the reversibility of zinc. These studies mainly focus on optimizing the structure of zinc anode, constructing artificial coatings on the zinc surface, and developing functional electrolyte additives. In particular, functional electrolyte additives, such as dimethyl sulfoxide, triacid citrate, ether, EDTA anion, glucose, ethylsulfonamide, xylitol, etc., have become a particularly effective and easy-to-operate strategy due to their wide sources. Functional electrolyte additives mainly improve the zinc anode / electrolyte interface through the following mechanisms: 1) Forming a SEI protective layer to prevent direct contact between the electrolyte and the zinc anode; 2) Adsorbing on the zinc metal surface, especially at the tip of the protrusion, to change the surface energy and enhance the interface stability.

[0005] In May 2022, Zhong Yun et al. designed a series of functional additives to optimize the electrolyte in the article "Study on Electrolyte Optimization for Improving the Stability of Aqueous Zinc-ion Battery Electrodes" to improve the cycle stability of aqueous zinc-ion battery electrodes. It was disclosed that adding 0.05M, 0.1M and 0.15M sodium glutamate to 2M ZnSO4 or 2M Zn(CF3SO3)2 electrolyte can inhibit interfacial side reactions and zinc dendrite growth, and improve the coulombic efficiency and cycle life of the zinc negative electrode. The best cycle life was shown when the amount of sodium glutamate added was 0.1 M, at 5 mA cm −2 (Current density) / 5 mAh cm −2 Under the test conditions of surface capacity, the cycle life of the assembled Zn||Zn symmetric battery can reach 1800h; in the electrolyte containing 0.1 M ZnSO4, at 2 mA cm −2 / 1 mAh cm −2 Under the test conditions, the average coulombic efficiency of the Zn||Cu half-cell can reach 99.75% and can be stably maintained for 1700 cycles.

[0006] In August 2023, Tang Xiaoning et al. proposed introducing glycine as an electrolyte additive into conventional aqueous ZnSO4 electrolytes in the article "Effects of Glycine Electrolyte Additives on the Electrochemical Performance of Aqueous Zinc Ion Batteries". The polar groups (-COOH and -NH2) in Gly can regulate the electrochemical performance of Zn 2+ The solvation structure of Zn 2+ The deposition of 50 mmol / L was sufficient to avoid the occurrence of dendrites and side reactions. −2 (Current density) / 1 mAh cm −2 Under the test conditions of surface capacity, the cycle life of the assembled Zn||Zn symmetrical battery can reach 3000h.

[0007] However, the above-mentioned functional additives can only provide unilateral limited protection for the zinc negative electrode, and during the battery cycle, the SEI film formed in situ may rupture or fall off from the zinc negative electrode, resulting in the electrolyte containing the additive still having limited improvement on the cycle stability of the aqueous zinc-ion battery. Summary of the invention

[0008] The object of the present invention is to provide an electrolyte for an aqueous zinc ion battery, so as to solve the problem that the aqueous zinc ion battery formed by the existing electrolyte has poor cycle stability.

[0009] The second object of the present invention is to provide an aqueous zinc ion battery to solve the problem of poor cycle stability of existing aqueous zinc ion batteries.

[0010] In order to solve the above-mentioned technical problems, the technical scheme of aqueous zinc ion battery electrolyte of the present invention is: An electrolyte for an aqueous zinc ion battery comprises a zinc salt and 5-15 mM BOC-D-glutamic acid.

[0011] The present invention is an improvement on the prior art, and provides an aqueous zinc ion battery electrolyte, by adding BOC-D-glutamic acid (C 10 H 17 NO6), BOC-D-glutamate can regulate the electrolyte solvation structure, modify the zinc anode / electrolyte interface, and in situ generate a solid electrolyte membrane SEI on the zinc anode surface, which has the characteristics of inhibiting dendrite growth, corrosion resistance, and slowing down hydrogen evolution reaction, and can greatly improve the cycle stability of aqueous zinc ion batteries.

[0012] In order to further inhibit the growth of zinc dendrites, preferably, the electrolyte consists of water, 1-1.5 M zinc salt, and 5-15 mM BOC-D-glutamate.

[0013] In order to further improve the cycle life of the aqueous zinc ion battery, preferably, the electrolyte consists of water, 1-1.5 M zinc salt, and 10-12 mM BOC-D-glutamate.

[0014] In order to further inhibit the growth of zinc dendrites, preferably, the zinc salt is ZnSO4.

[0015] The technical solution of the aqueous zinc ion battery of the present invention is: An aqueous zinc ion battery comprises the electrolyte for the aqueous zinc ion battery.

[0016] The aqueous zinc ion battery provided by the present invention adopts an electrolyte containing a BOC-D-glutamic acid additive and utilizes the effects of BOC-D-glutamic acid in inhibiting dendrite growth, resisting corrosion, and slowing down hydrogen evolution reaction, thereby greatly improving the cycle stability of the aqueous zinc ion battery. −2 / 5 mAh cm −2 Under the test conditions, the cycle life of the Zn||Zn symmetric battery can reach 2000h; at 1 mA cm −2 / 1 mAh cm −2 Under the test conditions, the cycle life of the Zn||Zn symmetric battery can reach 5750h. −2 / 1 mAh cm −2 Under the test conditions, the Zn||Cu half-cell can be cycled 1,300 times, and its average coulombic efficiency can reach 99.7%.

[0017] Preferably, the aqueous zinc ion battery is a zinc / zinc symmetric battery or a zinc / copper half-cell. BRIEF DESCRIPTION OF THE DRAWINGS

[0018] Figure 1 Figure 2 shows the Zn||Zn symmetric battery in electrolytes with different additive concentrations (1 mA cm −2 / 1 mAh cm −2 )Cycle life comparison chart; Figure 2 Symmetric Zn||Zn cells in different electrolytes (5 mA cm −2 / 5 mAh cm −2 )Cycle life comparison chart; Figure 3 Zn||Cu half-cell in different electrolytes (1 mA cm −2 / 1 mAh cm −2 )Cycle life comparison chart; Figure 4 The SEM morphology of zinc foil after cycling in different electrolytes; Figure 5 In-situ optical microscopy images of zinc foil after cycling in different electrolytes; Figure 6 Linear voltammetric scanning test graph and Tafel curve graph in different electrolytes; Figure 7 The Zn||Zn symmetric cell in the urea-doped electrolyte (1 mA cm −2 / 1 mAh cm −2 ) Cycle life diagram; Figure 8 For Zn||Cu half-cell in urea-doped electrolyte (1 mA cm −2 / 1 mAh cm −2 ) Cycle life diagram; Fig. 9 For the Zn||Zn symmetric cell in the electrolyte with mannitol (1 mA cm −2 / 1 mAh cm −2 ) Cycle life diagram; Fig.10 For Zn||Cu half-cell in mannitol-added electrolyte (1 mA cm −2 / 1 mAh cm −2 ) Cycle life diagram. DETAILED DESCRIPTION

[0019] The technical conception of aqueous zinc ion battery electrolyte of the present invention is as follows: In the electrochemical cycle of lithium-ion batteries, forming the SEI film through the reaction between the electrolyte and the negative electrode is a conventional method. This in-situ formed SEI plays a key role in maintaining the seamless adhesion of the electrode and has self-healing properties, which effectively prevents conditions that may cause electrode cracking and provides necessary protection for the negative electrode.

[0020] However, due to Zn 2+ / Zn (−0.76 V vs. SHE) has a high redox potential, and hydrogen evolution is inevitable during Zn electroplating, which poses a major challenge to the formation of a reliable SEI film on Zn.

[0021] The sodium glutamate additive used in the prior art produces free glutamate anions (Glu − ) reconstructs the zinc anode / electrolyte interface to form a water-poor double layer and occupies the active sites of zinc metal surface corrosion and hydrogen evolution reaction, which greatly inhibits water-induced side reactions, and can limit the 2D diffusion of zinc ions and promote [Zn(H2O)6] 2+ Desolvation enables uniform zinc deposition with low nucleation overpotential, thereby improving the reversibility and cycling stability of zinc-ion batteries; the polar groups (-COOH and -NH2) in glycine regulate the Zn 2+ The solvation structure of Zn 2+ deposition to avoid dendrites and side reactions.

[0022] The prior art sodium glutamate additive can only provide limited unilateral protection for the zinc negative electrode. It forms a double electrical layer at the zinc negative electrode / electrolyte interface, and the SEI film formed in situ may easily break or fall off from the zinc negative electrode during battery cycling. 10 H 17 NO6, structural formula as formula Ⅰ) additive, can reconstruct the hydrogen bond network in aqueous ZnSO4 electrolyte, and construct a unique Zn containing BOC-D-glutamic acid molecule 2+ -solvation structure, thereby inhibiting water-induced parasitic reactions. At the same time, BOC-D-glutamate molecules can be preferentially adsorbed on the zinc surface. The unique tert-butyl hydrophobic functional group on the molecule can also alleviate the corrosion of water in the electrolyte on the zinc negative electrode and inhibit side reactions. In addition, the anionic BOC-D-glutamate generates a solid electrolyte membrane SEI in situ on the surface of the zinc negative electrode, which can inhibit dendrite growth and induce uniform deposition of zinc on the zinc anode, and isolate water molecules. In summary, the introduction of the multifunctional BOC-D-glutamate additive can inhibit the growth of dendrites on the surface of the zinc negative electrode, reduce the corrosion current / potential, slow down the hydrogen evolution reaction, and greatly improve the cycle life of aqueous zinc-ion batteries.

[0023] Formula I The embodiments of the present invention are further described below in conjunction with specific examples. The chemical reagents involved in the following examples are all commercially available conventional products unless otherwise specified.

[0024] 1. Specific embodiments of the aqueous zinc ion battery electrolyte of the present invention The formulation composition of the aqueous zinc ion battery electrolyte of the present invention is shown in Table 1. The electrolyte is prepared by adding ZnSO4 and BOC-D-glutamic acid into water.

[0025] Table 1 Formula composition of electrolyte for aqueous zinc ion battery Example 1 Example 2 Example 3 <![CDATA[ZnSO4]]> 1 M 1 M 1 M BOC-D-Glutamate 5 mM 10 mM 15 mM water margin margin margin The aqueous zinc ion battery electrolyte of Example 1 is composed of water, 1 M zinc salt, and 5 mM BOC-D-glutamic acid.

[0026] The aqueous zinc ion battery electrolyte of Example 2 is composed of water, 1 M zinc salt, and 10 mM BOC-D-glutamic acid.

[0027] The aqueous zinc ion battery electrolyte of Example 3 is composed of water, 1 M zinc salt, and 15 mM BOC-D-glutamic acid.

[0028] 2. Specific embodiments of the aqueous zinc ion battery of the present invention Example 4 The aqueous zinc ion battery of this embodiment is a button cell, and the assembly method is as follows: The stainless steel spring sheet, stainless steel gasket, zinc sheet and diaphragm are stacked on the negative electrode shell in sequence, the electrolytes of Examples 1-3 are added dropwise respectively, and then the zinc sheet is stacked. Finally, the positive electrode shell is covered and transferred to a packaging machine for packaging to obtain a Zn||Zn symmetrical battery.

[0029] In other embodiments, a stainless steel spring sheet, a stainless steel gasket, a zinc sheet and a diaphragm are stacked on the negative electrode shell in sequence, and then the electrolytes of Examples 1-3 are respectively added and a copper sheet is superimposed. Finally, the positive electrode shell is covered and transferred to a packaging machine for packaging to obtain a Zn||Cu half-cell.

[0030] 3. Experimental Examples Experimental Example 1 This experimental example tests the cycling stability of zinc negative electrode in different electrolytes.

[0031] 1) Zn||Zn symmetric battery The cycling performance of the Zn||Zn symmetric battery was tested at a current density of 1 mA cm −2 , surface capacity is 1 mAhcm −2Under the test conditions, the cycle life comparison of Zn||Zn symmetric battery in electrolytes with different additive concentrations is shown in the figure below. Figure 1 As shown, from Figure 1 It can be seen that in the electrolyte without additives, the cycle life of the Zn||Zn symmetric battery is only about 100 h, and the cycle life in the electrolyte with the addition of BOC-D-glutamic acid (BDGO) is significantly improved, indicating that adding BOC-D-glutamic acid to the electrolyte can greatly improve the cycle stability of aqueous zinc-ion batteries.

[0032] In addition, with the increase of BOC-D-glutamic acid addition, the cycle life of the Zn||Zn symmetric battery first increases and then decreases. When the addition amount is 10 mM, it shows a higher cycle life and can achieve a stable cycle of more than 5750h. Compared with the prior art adding glycine electrolyte additive (50 mmol / L), under the same test conditions (1 mA cm −2 / 1mAh cm −2 The cycle life of the Zn||Zn symmetrical battery is 3000h. When the amount of additive added in the present invention is reduced by 80%, the cycle life is nearly doubled.

[0033] At a current density of 5 mA cm −2 , surface capacity of 5 mAh cm −2 Under the test conditions, the cycle life comparison of Zn||Zn symmetric battery is shown in the figure below. Figure 2 As shown, from Figure 2 It can be seen that in the electrolyte (ZnSO4@BDGO) with 10 mM BOC-D-glutamate added, the cycle life of the Zn||Zn symmetric battery exceeds 2000h, while in the electrolyte without additives, the Zn||Zn symmetric battery short-circuits in about 100 hours. Compared with the prior art adding sodium glutamate electrolyte additive (0.1M), under the same test conditions (5 mA cm −2 / 5 mAh cm −2 ) The cycle life of the Zn||Zn symmetrical battery is 1800h. When the amount of additive added in the present invention is reduced by one order of magnitude, the cycle life is increased by 11%.

[0034] 2) Zn||Cu half-cell Comparison of cycle life of Zn||Cu half-cell in different electrolytes Figure 3 As shown, from Figure 3 It can be seen that at a current density of 1 mA cm −2 , surface capacity of 1 mAh cm −2Under the test conditions, in the electrolyte (ZnSO4@BDGO) with 10 mM BOC-D-glutamate added, the Coulombic efficiency of the Zn||Cu half-cell reached 99.7% when it was cycled 1300 times.

[0035] Experimental Example 2 In this experiment, the surface morphology of zinc foil after cycling in 1 M ZnSO4 electrolyte without BOC-D-glutamate (Bare ZnSO4) and with 10 mM BOC-D-glutamate (ZnSO4@BDGO) was observed by scanning electron microscopy (SEM) and in situ optical microscopy. Figure 4-5 The SEM morphology and in-situ optical microscope images of zinc foil after cycling in different electrolytes are shown respectively.

[0036] from Figure 4 It can be seen that after 100 cycles in the electrolyte without additives, the surface of the zinc foil showed an uneven and loose morphology, accompanied by particle aggregation; while after 100 cycles in the ZnSO4@BDGO electrolyte, the surface deposition of the zinc foil was smoother and denser. Figure 5 The detailed process of zinc dendrite growth in different electrolytes was demonstrated. After cycling in an electrolyte without additives, mossy zinc with obvious protrusions was visible on the zinc foil after 60 minutes; while in the ZnSO4@BDGO electrolyte, the surface of the zinc foil remained dense and uniform even after 60 minutes, fully demonstrating the potential of BOC-D-glutamate additives in improving the performance of aqueous zinc-ion batteries.

[0037] Experimental Example 3 This experiment uses an electrochemical workstation to test and evaluate the ability of different electrolytes to inhibit side reactions. The linear voltammetric scan test graphs in different electrolytes ( Figure 6 a) and Tafel curve diagram ( Figure 6 b) If Figure 6 As shown. Figure 6 It can be seen that in the ZnSO4@BDGO electrolyte, the hydrogen evolution reaction on the zinc anode surface is significantly reduced (see Figure 6 a); Figure 6 b shows that the presence of BOC-D-glutamic acid additive leads to an increase in the zinc corrosion potential from -17 mV to -12 mV and an increase in the corrosion current from 5.86 μA cm -2 Reduced to 1.183 μA cm -2 ,These results indicate that in the ZnSO4@BDGO electrolyte, the corrosion reaction tends to weaken and the corrosion rate is low.

[0038] Experimental Example 4 This experimental example illustrates the screening of electrolyte additives.

[0039] The additives were screened by testing the cycling performance of batteries made with electrolytes containing other additives, including urea and mannitol.

[0040] The specific screening results are as follows: using 20 mM urea as the electrolyte additive, the prepared aqueous zinc ion battery has a high −2 / 1 mAh cm −2 Under the test conditions, the cycle life of the Zn||Zn symmetrical battery is 500h (see Figure 7 ); Zn||Cu half-cell can be cycled 550 times, and its average coulombic efficiency can reach 98.97% (see Figure 8 ).

[0041] The aqueous zinc ion battery prepared by using 20 mM mannitol as the electrolyte additive has a high −2 / 1mAh cm −2 Under the test conditions, the cycle life of the Zn||Zn symmetrical battery is 1600h (see Fig. 9 ); at 1 mA cm −2 / 1 mAhcm −2 Under the test conditions, the Zn||Cu half-cell can be cycled 400 times, and its average coulombic efficiency can reach 99.63% (see Fig.10 ).

[0042] Compared with urea and mannitol, the BOC-D-glutamic acid additive provided by the present invention can better improve the cycle life of aqueous zinc ion batteries.

[0043] Finally, it should be noted that the above is only a preferred embodiment of the present invention and is not intended to limit the present invention. Although the present invention has been described in detail with reference to the aforementioned embodiments, it is still possible for those skilled in the art to modify the technical solutions described in the aforementioned embodiments or to make equivalent substitutions for some of the technical features therein. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principles of the present invention should be included in the protection scope of the present invention.

Claims

1. An aqueous zinc ion battery electrolyte, characterized in that Includes zinc salt and 5~15mM BOC-D-glutamate.

2. The aqueous zinc ion battery electrolyte according to claim 1, wherein The electrolyte consists of water, 1-1.5 M zinc salt, and 5-15 mM BOC-D-glutamic acid.

3. The aqueous zinc ion battery electrolyte according to claim 1 or 2, wherein: The electrolyte consists of water, 1-1.5 M zinc salt, and 10-12 mM BOC-D-glutamic acid.

4. The aqueous zinc ion battery electrolyte according to claim 1, wherein The zinc salt is ZnSO4.

5. An aqueous zinc ion battery, characterized in that: The invention comprises the electrolyte for aqueous zinc ion battery according to any one of claims 1 to 4.

6. The aqueous zinc ion battery according to claim 5, characterized in that: The aqueous zinc ion battery is a zinc / zinc symmetrical battery or a zinc / copper half-cell.